Biomechanical analysis of gait with double backpack - Santos, Jorge (2018)
When observing the gait associated with the transportation of backpacks by children and adults, there were differences in posture and gait when compared to gait without back overload. Over time, the problem seems to get worse. Access to information technology, contrary to expectations, has aggravated the problem because people carry in their daily lives more electronic equipment of a non-negligible weight. If we take as example of the military soldiers, they carry some of the material in a bag next to their chest. Using a backpack type double backpack, studies suggest its performance is better than traditional transport. This solution has not been systematically studied for the civilian population .The goal of this work is to study the problem of the transport of a non-negligible load, on the back, during a distance corresponding to a journey. Check for the advantages of using a double backpack. The method used is biomechanics. Will be analyzed the several parameters of gait in particular will be used electromyography, thermography and kinetics. For this study, we will take healthy young adults with ages between 18 to 30 and it is expected to confirm the advantages of using double backpack by the civilian population for the transport of high loads minimizing possible future injuries.